Testing some European fish-based assessment systems using Slovenian fish data from the Ecoregion Alps - Gorazd Urbanič; Samo Podgornik (Natura Sloveniae)
The European Fish Index (EFI), the Fish Index Austria (FIA) and the German fish-based assessment system (FiBS) were tested using Slovenian fish data. Fish were sampled using electric fishing procedure in small and medium sized rivers of the Danube river basin in the Ecoregion Alps. To test the appropriateness of selected indices, correlations between hydromorphological alteration pressure and fish indices were calculated. Hydromorphological alteration pressure was defined using seven Slovenian hydromorphological quality classes. Correlations were positive and statistically significant in all cases but the coefficient of determination (R2) was very low, not exceeding 0.15. The highest R2 was calculated using FIA without the biomass knockout criterion. Possible reasons for the low R2 values including criteria for the hydromorphological alteration classes, fishery management influence and tested fish indices, are discussed. In addition, appropriateness of the inclusion of allochthonous fish species in the fish-based assessment systems is discussed